Anatomical and Technical Considerations of "Dual Subsartorial Block" (DSB), A Novel Motor-sparing Regional Analgesia Technique for Total Knee Arthroplasty - Kartik Sonawane; Hrudini Dixit; Tuhin Mistry; J. Balavenkatasubramanian (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2021)
Background: The modernization of arthroplasty has paved the way for the resurgence of ultrasound-guided regional analgesia (RA) techniques. The evolution of newer RA techniques aids in reducing postoperative pain considerably as well as facilitates early ambulation and discharge. "Dual Subsartorial Block (DSB)" is recently described as a novel procedure-specific, motor-sparing, and opioid-sparing RA technique for total knee arthroplasty (TKA) surgery. This review article highlights the innervations covered by DSB based on the anatomical considerations and its suitability for providing analgesic coverage in TKA with medial approaches.  Methodology: We describe anatomical considerations based on the available literature about the anatomy related to the femoral triangle, adductor canal, and subsartorial region. The technical consideration of the DSB is based on our observations of the ongoing study on  patients undergoing TKA with medial approaches. However, other details of the study are not part of this article. Results: After studying the anatomical and technical aspects of the DSB, it is possible to cover almost all procedure-specific innervations of TKA surgeries with the DSB. Our observations and statistical analysis found DSB as a procedure-specific, motor-sparing, and opioid-sparing RA technique.  Discussion: We describe the complex anatomy of the femoral triangle and adductor canal block along with sonoanatomical variations of various subsartorial regions. We also elaborate on the technical details, analgesic coverage, and possible complications of DSB.